Gender bias and inequity holds women back in their conservation careers - James, Robyn; Fisher, Jonathan R. B.; Carlos-Grotjahn, Chelsea; Boylan, Marissa S.; Dembereldash, Baigalmaa; Demissie, Meaza Z.; Diaz De Villegas, Crystal; Gibbs, Bridget; Konia, Ruth; Lyons, Kristen; Possingham, Hugh; Robinson, Cathy J.; et al. (Frontiers in Environmental Science, 2023)
The planet is facing climate and biodiversity loss crises that impact all of humanity and yet globally, women remain underrepresented in leading solutions to these urgent conservation challenges. As one of the world’s largest conservation non-profit organizations, The Nature Conservancy (TNC) provided a large case-study for understanding inequity for women in the conservation sector. In 2018, all 1,789 conservation and science staff at TNC were surveyed to understand how they are able to develop their careers and contribute to conservation research and decision making. Of the 904 responses (490 men and 414 women), results show that men influence conservation and science decisions more than women; women face multiple barriers across their conservation careers due to gender bias; women experience sexual harassment and discrimination, as well as fear retaliation more than men; and men reported the sector as a more equitable and favorable place for women than women themselves experienced. Our data demonstrates that gender equality (equal representation of men and women) does not automatically mean that women no longer face systemic inequity and that intersectional issues such as race, location and caring responsibilities can all make it even more difficult for women to excel. Respondents drew from experiences across their conservation careers, to suggest how the conservation sector could address these issues. Based on our findings, we recommend practical ways the conservation sector can improve gender equity, including via workplace and cultural change measures, as well as changes to recruitment, pay transparency, and career development policies.